The Study on Timolol and Its Potential Phototoxicity Using Chemical, In Silico and In Vitro Methods - Karolina Lejwoda; Anna Gumieniczek; Agata Filip; Beata Naumczuk (MDPI AG, 2024)
Timolol (TIM) is a non-selective ß-adrenergic receptor antagonist used orally for the treatment of hypertension and heart attacks, and topically for treating glaucoma; lately, it has also been used in some specific dermatological problems. In the present study, its photodegradation and potential risk of phototoxicity were examined using chemical, in silico and in vitro methods. The UV/VIS irradiated solutions of TIM at pH 1-13 were subjected to LC-UV and UPLC-HRMS/MS analyses showing pseudo first-order kinetics of degradation and several degradation products. The structures of these photodegradants were elucidated by fragmentation path analysis based on high resolution (HR) fragmentation mass spectra, and then used for toxicity evaluation using OSIRIS Property Explorer and Toxtree. Potential risk of phototoxicity was also studied using chemical tests for detecting ROS under UV/VIS irradiation and in vitro tests on BALB/c 3T3 mouse fibroblasts (MTT, NRU and Live/Dead tests). TIM was shown to be potentially phototoxic because of its UV/VIS absorptive properties and generation ROS during irradiation. As was observed in the MTT and NRU tests, the co-treatment of fibroblasts with TIM and UV/VIS light inhibited cell viability, especially when concentrations of the drug were higher than 50 µg/mL.